Ecological restoration of reclaimed wastewater lakes using submerged plants and zooplankton. (27th March 2013) - Li, Kejun; He, Wenhui; Hu, Qian; Gao, Song
Abstract High‐pollutant concentrations have led to the breakout of planktonic bloom and the breakdown of the ecosystem in many lakes in China and other countries. The removal of the organic and inorganic pollutants from industrial, agricultural and domestic wastewater and the restoration of the aquatic ecosystem of the polluted water bodies are persistent issues. Constructed wetlands are often used, and most depend on emerged plants. In this study, Daphnia magna, a type of zooplankton, and five species of submerged plants were used to remove nitrogen and phosphorus from reclaimed domestic wastewater in four scenery lakes of a garden in Peking, China. Water quality was assessed by the local environmental inspection station as the government inspection and a commercial company as the third party inspection, and the gathered data proved that ecological restoration was successful in this study.